Cost of type 2 diabetes mellitus management for households in Northern India – an econometric analysis - Kanika Bansal; Meena Rajput; Rajesh Rajput (BMC Health Services Research)
Abstract Aim To estimate the economic burden of type 2 Diabetes Mellitus management and its influencing variables, on urban households in North India. Methods A community-based prospective, observational, cost-of-illness study was carried out from the patient’s perspective, in urban Rohtak, Haryana. Probit, GLM (log link with gamma) and two-part regression techniques were used to model predictors of cost estimates. Results Catastrophic health expenditure (CHE) due to T2DM management, was experienced by 10.14% of patients, and 19.59% faced impoverishment. The normalized poverty gap increased by 4.34% post-payment for T2DM as compared to pre-payment. The total cost was ₹17,113 per annum and out-of-pocket payments were ₹10,424. Direct medical cost formed the biggest portion i.e., 54.65% of total cost, whereas direct non-medical cost was 6.26%, and indirect cost was 39.09%. Majority of the total spending was attributed to drugs (42.39%). Insulin therapy, complications, socio-economic status and age at diagnosis were the most common significant predictors of economic burden. Conclusions The economic burden of diabetes in India is substantial, driven by both direct medical costs and indirect costs such as lost productivity. This high cost is responsible for significant CHE, impoverishment and deepening poverty gap. The study underscores the urgent need for comprehensive and cost-effective management strategies to mitigate the long-term economic impact of T2DM on urban households.